2017
DOI: 10.18632/oncotarget.15450
|View full text |Cite
|
Sign up to set email alerts
|

The miR-25-93-106b cluster regulates tumor metastasis and immune evasion via modulation of CXCL12 and PD-L1

Abstract: The stromal microenvironment controls response to injury and inflammation, and is also an important determinant of cancer cell behavior. However, our understanding of its modulation by miRNA (miR) and their respective targets is still sparse. Here, we identified the miR-25-93-106b cluster and two new target genes as critical drivers for metastasis and immune evasion of cancer cells. Using miR-25-93-106b knockout mice or antagomiRs, we demonstrated regulation of the production of the chemoattractant CXCL12 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 58 publications
3
47
0
Order By: Relevance
“…The mammalian target of rapamycin signaling inhibitor miR-140 exhibits immune-mediated antitumor effect via inhibiting PD-L1 expression. This miRNA cluster inhibits the receptiveness of bone marrow stromal niche to metastatic cancer cells through targeting CXCL12 [75]. The level of miR-140 was markedly downregulated in osteosarcoma [72].…”
Section: Mirnas Regulation Of Mdscsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mammalian target of rapamycin signaling inhibitor miR-140 exhibits immune-mediated antitumor effect via inhibiting PD-L1 expression. This miRNA cluster inhibits the receptiveness of bone marrow stromal niche to metastatic cancer cells through targeting CXCL12 [75]. The level of miR-140 was markedly downregulated in osteosarcoma [72].…”
Section: Mirnas Regulation Of Mdscsmentioning
confidence: 99%
“…Such inhibition enriches the tumor microenvironment with CD8+ antitumor T cells and reduces the infiltration of MDSCs. The percentage of PD-L1+ myeloid cells has been shown to be higher in miR-25-93-106b knockout mice in comparison to wild-type mice [75]. The immunosuppressive potential of MDSCs in CRC is opposed by the effect of miR-20a/ miR-17-5p on STAT3 [73].…”
Section: Mirnas Regulation Of Mdscsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Gao et al (2018) reported the oncogenic function of the miR-144/451 cluster in esophageal cancer by using miRNA mimics (Gao et al, 2018). Cioffi et al, 2017, demonstrated the biological function of the miR-25/106b cluster using miRNA mimics (Cioffi et al, 2017). Using miR-214 mimics, Wang, Zhao, et al (2016), demonstrated tumor suppressive nature of miR-214/199a/199a* in hepatocellular carcinoma (Wang, Xie, Tan, Li, & Xie, 2016).…”
Section: Resistance To Treatment (Radio-and Chemoresistance)mentioning
confidence: 99%
“…Antagomirs have been successfully used to block the expression of oncomirs (Wen, Danquah, Chaudhary, & Mahato, 2015). For instance, treating the cells with antagomiR for miR-25 and 93, members of the miR-25/106b cluster enhanced the migration and invasion of bone marrow cells (Cioffi et al, 2017). Overexpression of mir-17/92 promotes the development and progression of pancreatic ductal adenocarcinoma (Quattrochi et al, 2017).…”
Section: Resistance To Treatment (Radio-and Chemoresistance)mentioning
confidence: 99%